Investigating the Synthesis of Activated Carbon from Carbon Chips of Carbon Fibre Reinforced Polymer for the removal of Methylene Blue - Fathi, Farhah Rusyda; Amir, Dzilal; Abd Halim, Nor Farah Huda; Nasaruddin, Ricca Rahman (Springer, 2022)
The milling operation of carbon fiber-reinforced polymers (CFRP) generates waste named carbon chips (CC) which could be converted into value-added products such as activated carbon (AC). In this study, we synthesized AC from the CC of CFRP. The effects of the mass ratio of raw materials and activating agent, reaction temperature, and the concentration of acid in the washing step, on the yield of AC and the removal of methylene blue in solution were investigated. The results show that CC from CFRP gave higher yield and performance when compared to AC produced from durian skin (DS) and CC-DS mixture. Higher reaction temperature (600 °C) and 5% concentration of nitric acid (HNO3) resulted in the highest yield and methylene blue (MB) adsorption percentage of the AC. As AC is widely used in many applications such as water and air remediations, this study can significantly promote the use of CC, the CFRP waste as raw materials for the AC synthesis